Effect of intra-organizational factors on research - Farajollahi, Alireza; Sedagat, Kamran; Alizadeh, Mahasti; Imanzad, Masoumeh; Ashrafi Hafez, Asghar (Archives of Advances in Biosciences, 2014)
Along with other areas in our country, the research in medical sciences is a necessity for the maintenance and improvement of community health. The objectives of this study were to determine the intra-organizational factors of conducting research in Tabriz University of Medical Sciences. The matrix of the study included entire academic members and research staff of the university where 121 of them were selected randomly for a descriptive cross sectional study. A questionnaire was designed to collect data using Likert Spectrum. The major difficulty was the lack of sufficient free time. Significant differences were seen in respect with the access to facilities and conducting research, assessing expected benefits of conducting research, level of research awareness among academic members with and without research project. Differences in respect with motivation force, collaboration, job satisfaction and expected benefits from conducting research were shown to be not significant. As stated by academic members, their problems involved with conducting research projects provides lesser role of intra-organizational factors compared to that of personal factors. In other words, the most major problems in not doing research are the lack of sufficient time and proper skills in research method and innovation in looking for problems to be solved.